Piper betle: a review on its bioactive compounds, pharmacological properties, and extraction process - N. I., Azahar; Nadzirah, Mohd Mokhtar; Mohd Azmir, Arifin (IOP Publishing, 2020)
Piper betle is a well-known medicinal plant that cultivated primarily in Southeast Asia. This plant is made up of a large number of bioactive compounds such as tannins, flavonoids (quercetin), eugenol, hydroxychavicol and chavibetol that represent the major components of the plant. This plant has been extensively studied for its pharmacological properties such as antimicrobial, anticancer, antioxidant, antidiabetic and anticancer. Many techniques have been used in Piper betle extraction such as soxhlet extraction, sonication extraction, maceration, ultrasound assisted extraction (UAE), supercritical fluid extraction (SFE) and microwave assisted extraction (MAE). Various benefits of Piper betle extract have been well utilized by the production of numerous types of plant-based products and to date, research on new products based on Piper betle is still being done. Application of Piper betle extract resulting in wide possibilities of usage in future product development. The quality and safety of Piper betle studies provide by toxicity test shows the Piper betle extract exhibit little to none toxicity level at respective concentration. This article aims to present a review of previous studies and research works conducted on Piper betle to serve as a source of additional information for future research related to the Piper betle.